2018
DOI: 10.18203/2319-2003.ijbcp20180097
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of pattern of adverse drug reactions of cardiovascular drugs in a tertiary care institute

Abstract: INTRODUCTIONWorldwide, the number of deaths from cardiovascular diseases (CVDs) was estimated at 17.3 million per year, and it is expected to increase to approximately 23.6 million patients by 2030.1 While the prevalence and mortality due to CHD is declining in the developed nations the same cannot be held true for developing countries. There has been an alarming increase over the past two decades in the prevalence of CHD and cardiovascular mortality in India and other south Asian countries. 2 The incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…This finding is similar to the study done by Wankhede et al, where they report the most ADRs were scored as possible (96%). 42 Most of the patients had moderate ADRs (60%) and mild (40%) according to severity scale which is comparable to the study conducted by Sriram S et al, where they observed the severity of 49% of reactions (using Hartwig scale) was reported as moderate. 43 Most of the ADRs were not preventable (60%) followed by preventable (40%) according to the Schumock and Thornton.…”
Section: Drug Related Problemssupporting
confidence: 85%
“…This finding is similar to the study done by Wankhede et al, where they report the most ADRs were scored as possible (96%). 42 Most of the patients had moderate ADRs (60%) and mild (40%) according to severity scale which is comparable to the study conducted by Sriram S et al, where they observed the severity of 49% of reactions (using Hartwig scale) was reported as moderate. 43 Most of the ADRs were not preventable (60%) followed by preventable (40%) according to the Schumock and Thornton.…”
Section: Drug Related Problemssupporting
confidence: 85%
“…Gagal jantung kongestif adalah sindrom klinis progresif yang disebabkan oleh ketidakmampuan jantung dalam memompa darah untuk memenuhi kebutuhan metabolisme tubuh (Wells, Dipiro, Schwinghammer, & Dipiro, 2015). Gagal jantung adalah sindrom yang umum, membutuhkan biaya yang mahal dan dapat menyebabkan kelemahan bagi pasienn yang dikaitkan dengan rejimen obat yang sangat kompleks dan banyaknya komorbiditas (Wankhede, Pardeshi, Ghorpade, & Ghongane, 2018) Obat-obat yang digunakan untuk penatalaksanaan penyakit kardiovaskular tidak serta merta tanpa efek samping, tetapi justru dapat menyebabkan konsekuensi yang merugikan jika tidak dipantau dengan benar. Meningkatnya jumlah obat pada pasien jantung menimbulkan adanya kecenderungan untuk menyebabkan masalah terkait obat seperti ADRs, interaksi obat antar obat, dll.…”
Section: Pendahuluanunclassified